Analysis of Early Childhood Education Background on Adaptation and Adjustment Skills in the Kindergarten Environment: A Comparative Study Between PAUD and Non-PAUD Graduates - Abdulloh Aziz Assa'diy; Sevira Putri Rosa (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2026)
Early Childhood Education (ECE) plays an important role in preparing children to enter formal education, particularly in terms of their ability to adapt and adjust to the school environment. This article aims to analyze comparatively the adaptation and adjustment abilities of children aged 5–6 years based on their educational background, namely between ECE graduates and non-ECE graduates. This study employed a qualitative approach with a comparative study design. Data were collected through direct observation of children’s behavior during learning and play activities in the kindergarten classroom, focusing on aspects of environmental adaptation, social interaction, emotional regulation, and creativity in play. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that children who graduated from ECE demonstrated better adaptation skills, as indicated by their readiness to face the school environment, understanding of classroom routines, independence, and compliance with rules. In addition, ECE graduates showed more developed social-emotional adjustment and higher creativity in play compared to non-ECE children. These findings confirm that ECE contributes positively to preparing children for the kindergarten environment and supports children’s holistic development.